Green Marketing Campaign and Loyalty Customer : A study from Starbucks Makassar Customers - Aslam, Annisa Paramaswary; Parawansa, Dian Anggraece Sigit; Putra, Muh Al Fatah Arief (PT. Maju Malaqbi Makkarana, 2023)
The purpose of this study to see the effect of the campaigning for green marketing. This research aims to determine the effect of green marketing, service quality on customer loyalty through customer satisfaction as an intervening variable. The method used is a quantitative method with descriptive and causality research types, as well as the SEM-PLS analysis method. The final sample was 224 Starbucks Coffee customers in Makassar City. Based on the results of the study it was concluded that green marketing and service quality have a positive and significant effect on customer loyalty either directly or through customer satisfaction as an intervening variable.